Review paperEstablished and emerging variants of glioblastoma multiforme: review of morphological and molecular features - Karsy, Michael; Gelbman, Marshall; Shah, Paarth; Balumbu, Odessa; Moy, Fred; Arslan, Erol (Folia Neuropathologica, 2012)
Since the recent publication of the World Health Organization brain tumour classification guidelines in 2007, a significant expansion in the molecular understanding of glioblastoma multiforme (GBM) and its pathological as well as genomic variants has been evident. The purpose of this review article is to evaluate the histopathological, molecular and clinical features surrounding emerging and currently established GBM variants. The tumours discussed include classic glioblastoma multiforme and its four genomic variants, proneural, neural, mesenchymal, classical, as well as gliosarcoma (GS), and giant cell GBM (gcGBM). Furthermore, the emerging variants include fibrillary/epithelial GBM, small cell astrocytoma (SCA), GBM with oligodendroglial component (GBMO), GBM with primitive neuroectodermal features (GBM-PNET), gemistocytic astrocytoma (GA), granular cell astrocytoma (GCA), and paediatric high-grade glioma (HGG) as well as diffuse intrinsic pontine glioma (DIPG). Better understanding of the heterogeneous nature of GBM may provide improved treatment paradigms, prognostic classification, and approaches towards molecularly targeted treatments.